ANALISIS KADAR TIMBAL (Pb) PADA BEDAK PADAT YANG BEREDAR DI BANJARMASIN MENGGUNAKAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Huzaeroh, Anifatu; Lestari, Yulianita Pratiwi Indah; Hayati, Mardia (Jurnal Insan Farmasi Indonesia, 2024)
Pressed powder is a type of cosmetic that is commonly used and its safety must be guaranteed so that it is free from contamination. The aim of this research is to determine the presence of lead (Pb) contamination content in solid powder circulating in Banjarmasin using the absorption spectrophotometry method. atom. The test methods used include qualitative tests using 1 M NaOH reagent and quantitative tests that have been validated using Atomic Absorption Spectrophotometry. The results of the qualitative test showed that the five samples were reactive after being reacted with 1 M NaOH and produced a white precipitate. The method validation test results show that this method has linearity with a value of R=0.9996, LOD=0,019994243 ppm and LOQ=0,06664748 ppm. From the qualitative test, it was found that the five samples were indicated to contain lead, therefore it was continued with quantitative testing. Quantitative test results showed lead levels in samples coded A, B, C, D and E were 3,346 mg/kg; 4,894 mg/kg; 3,920 mg/kg; 3,284 mg/kg; dan 1,829 mg/kg.  It can be concluded that although there is still solid powder that contains lead (Pb), it is still below the safe limit for lead contamination, namely <20 mg/kg.